Participation of retroelements in chromoanagenesis in cancer development - R. N. Mustafin (Сибирский онкологический журнал)
Purpose of the study: to determine the role of retroelements in chromoanagenesis mechanisms in cancer etiopathogenesis.Material and Methods. The search for relevant sources was carried out in the Scopus, Web of Science, PubMed, Elibrary systems, including publications from February 2002 to December 2023. Of the 864 scientifc articles found, 60 were used to write a systematic review.Results. According to original works and meta-analyses results, the cause of complex chromosomal rearrangements during cancer development may be retroelement pathological activation. Chromoanagenesis involves LINE1, SVA, Alu, HERV, which cause double-stranded DNA breaks, insertions in tumor suppressor genes region, the formation of chimeric oncogenes due to retroelement use as new promoters, and function as molecular “band-aids” in non-homologous end junctions and form bridges of distal DNA fragments. Global structural rearrangements of chromosomes observed during chromoanagenesis may be consequences of retroelements activation, which participate in non-allelic homologous recombination and in microhomology-mediated joining of ends characteristic. Certain types of neoplasms, such as colon cancer, are characterized by both high levels of chromothripsis and retroelement activity. In head and neck squamous cell carcinoma, chromoplexy is specifc, the sources of sequences at the breakpoints of which are retroelements. During chromoanagenesis, activation of proto-oncogenes and inactivation of tumor suppressor genes are observed, which is also a consequence of retroelement activation. This is due to the presence of retroelement sequences in proto-oncogenes promoter regions and introns (which become the basis for chimeric oncogene formation) and hot spots of insertional mutagenesis in tumor suppressor genes (transpositions into these regions inactivate these genes).Conclusion. The results obtained on the driver effect of retroelements in chromothripsis, chromoplexy and chromoanasynthesis mechanisms, which are the basis for the formation of clonal evolution of tumors, indicate promise of targeted therapy aimed at silencing the activity of retroelements in cancer patients treatment. For this purpose, it is possible to use microRNAs complementary to retroelements, which are also involved in tumor development, as tools.